Patterns of Symbiodinium (Dinophyceae) diversity and assemblages among diverse hosts and the coral reef environment of Lizard Island, Australia. Issue 4 (22nd June 2018) - Ziegler, Maren; Stone, Elizabeth; Colman, Daniel; Takacs‐Vesbach, Cristina; Shepherd, Ursula
Abstract : Large‐scale environmental disturbances may impact both partners in coral host– Symbiodinium systems. Elucidation of the assembly patterns in such complex and interdependent communities may enable better prediction of environmental impacts across coral reef ecosystems. In this study, we investigated how the community composition and diversity of dinoflagellate symbionts in the genus Symbiodinium were distributed among 12 host species from six taxonomic orders (Actinaria, Alcyonacea, Miliolida, Porifera, Rhizostoma, Scleractinia) and in the reef water and sediments at Lizard Island, Great Barrier Reef before the 3rd Global Coral Bleaching Event. 454 pyrosequencing of the ITS2 region of Symbiodinium yielded 83 operational taxonomic units (OTUs) at a 97% similarity cut‐off. Approximately half of the Symbiodinium OTUs from reef water or sediments were also present in symbio. OTUs belonged to six clades (A‐D, F‐G), but community structure was uneven. The two most abundant OTUs (100% matches to types C1 and A3) comprised 91% of reads and OTU C1 was shared by all species. However, sequence‐based analysis of these dominant OTUs revealed host species specificity, suggesting that genetic similarity cut‐offs of Symbiodinium ITS2 data sets need careful evaluation. Of the less abundant OTUs, roughly half occurred at only one site or in one species and the background Symbiodinium communities were distinct between individual samples. We conclude that sampling multiple host taxa with differing life history traits will be critical to fully understand the symbiont diversity of a given system and to predict coral ecosystem responses to environmental change and disturbance considering the differential stress response of the taxa within.